Epithelioid hemangioma (angiolymphoid hyperplasia with eosinophilia) in the oral mucosa - Anshul Aggarwal; Vaishali Keluskar (Indian Journal of Dental Research, 2012)
Angiolymphoid hyperplasia with an eosinophilia (ALHE) is a rare benign entity whose etiology and pathogenesis is under debate. Clinically, it is characterised by cutaneous papules or nodules on the head and neck. Literature reveals very few cases of this entity in the oral mucosa. Here, we report a case of ALHE in a 25 year-old woman, who presented with a painless, 5mm x 5mm, sub mucosal erythematous nodule on left angle of mouth at lower lip. Histological examination of lip biopsy specimens revealed an increase in small vessels. The vascular walls consist of prominent endothelial cells with a histiocytoid appearance, which protruded into the lumen. Many eosinophils and lymphocytes were also seen around the vessels. The diagnosis of ALHE was made from the above findings.